Implementasi Teori Pembelajaran Blended Learning dalam Menyeimbangkan Kapabilitas Belajar pada Era Digital (Studi Kasus di Prodi PAI Universitas Alma Ata Yogyakarta) - Abdul Rohman; Mastu Anwar Hartanto (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2020)
Blended learning learning pattern is a combination of conventional learning patterns and e-learning. The concept of blended learning applied at the University of Alma-ata uses the WEB system with a composition of blended learning patterns, 75% for conventional learning and 25% for e-learning. The implementation of the blended learning theory in balancing learning capabilities includes two classifications. Learning capabilities include five aspects, namely verbal information, cognitive strategies, intellectual skills, attitudes and motor skills. The five capabilities are divided into two classifications of blended learning theory, namely verbal information and cognitive strategies included in the classification of e-learning, this is because it places more emphasis on the knowledge aspect. Then the three other aspects fall into the classification of conventional learning, this is because the conventional learning process is carried out directly and face-to-face between educators and students, educators become a central figure in learning and play a role not only in conveying science but as explained by Alghazali, educators are al -mudaris, al-mualim, al-muaddib and al-walid.